Comparative study between wear of uncoated and TiAlN-coated carbide tools in milling of Ti6Al4V - Uddin, M.; Pham, B.; Sarhan, A.; Basak, A.; Pramanik, Alokesh (Springer Science + Business Media, 2017)
As is recognized widely, tool wear is a major problem in the machining of difficult-to-cut titanium alloys. Therefore, it is of significant interest and importance to understand and determine quantitatively and qualitatively tool wear evolution and the underlying wear mechanisms. The main aim of this paper is to investigate and analyse wear, wear mechanisms and surface and chip generation of uncoated and TiAlN-coated carbide tools in a dry milling of Ti6Al4V alloys. The quantitative flank wear and roughness were measured and recorded. Optical and scanning electron microscopy (SEM) observations of the tool cutting edge, machined surface and chips were conducted. The results show that the TiAlN-coated tool exhibits an approximately 44% longer tool life than the uncoated tool at a cutting distance of 16 m. A more regular progressive abrasion between the flank face of the tool and the workpiece is found to be the underlying wear mechanism. The TiAlN-coated tool generates a smooth machined surface with 31% lower roughness than the uncoated tool. As is expected, both tools generate serrated chips. However, the burnt chips with blue color are noticed for the uncoated tool as the cutting continues further. The results are shown to be consistent with observation of other researchers, and further imply that coated tools with appropriate combinations of cutting parameters would be able to increase the tool life in cutting of titanium alloys.